Rac and Rab GTPases dual effector Nischarin regulates vesicle maturation to facilitate survival of intracellular bacteria. (5th February 2013) - Kuijl, Coenraad; Pilli, Manohar; Alahari, Suresh K; Janssen, Hans; Khoo, Poh‐Sim; Ervin, Karen E; Calero, Monica; Jonnalagadda, Sobhanaditya; Scheller, Richard H; Neefjes, Jacques; Junutula, Jagath R
<x xml:space="preserve">Abstract</x> The intracellular pathogenic bacterium Salmonella enterica serovar typhimurium (Salmonella) relies on acidification of the Salmonella‐containing vacuole (SCV) for survival inside host cells. The transport and fusion of membrane‐bound compartments in a cell is regulated by small GTPases, including Rac and members of the Rab GTPase family, and their effector proteins. However, the role of these components in survival of intracellular pathogens is not completely understood. Here, we identify Nischarin as a novel dual effector that can interact with members of Rac and Rab GTPase (Rab4, Rab14 and Rab9) families at different endosomal compartments. Nischarin interacts with GTP‐bound Rab14 and PI(3)P to direct the maturation of early endosomes to Rab9/CD63‐containing late endosomes. Nischarin is recruited to the SCV in a Rab14‐dependent manner and enhances acidification of the SCV. Depletion of Nischarin or the Nischarin binding partners—Rac1, Rab14 and Rab9 GTPases—reduced the intracellular growth of Salmonella. Thus, interaction of Nischarin with GTPases may regulate maturation and subsequent acidification of vacuoles produced after phagocytosis of pathogens.